194k views
1 vote
Y=-2x+2 Y=-2x-2 state the solution

User Joya
by
5.2k points

2 Answers

3 votes

Answer:

NO SOLUTION.

Explanation:

As both the expressions in x are equal to y we can write:

-2x + 2 = -2x - 2 Adding 2x and - 2 to both sides:

-2x + 2 + 2x - 2 = -2x + 2x - 2 -2

-2x + 2x = -2 - 2

0 = -4

- which is absurd so there is NO SOLUTION to this system of equations.

User Edward Newell
by
4.6k points
1 vote

Answer:

Explanation:

Y=-2x+2.....(1)

Y=-2x-2.....(2)

Subtracting (1) from (2)

Y - Y = -2x - (-2x) -2 - 2

O = -2x + 2x - 4

O = 0 - 4

Hence it as no solution the the two variables tend to zero

User Cookandy
by
3.8k points